Real term premia in consumption-based models - Errikos Melissinos (Leibniz Institute for Financial Research SAFE, 2024)
Can consumption-based mechanisms generate positive and time-varying real term premia as we see in the data? I show that only models with time-varying risk aversion or models with high consumption risk can independently produce these patterns. The latter explanation has not been analysed before with respect to real term premia, and it relies on a small group of investors exposed to high consumption risk. Additionally, it can give rise to a "consumption-based arbitrageur" story of term premia. In relation to preferences, I consider models with both time-separable and recursive utility functions. Specifically for recursive utility, I introduce a novel perturbation solution method in terms of the intertemporal elasticity of substitution. This approach has not been used before in such models, it is easy to implement, and it allows a wide range of values for the parameter of intertemporal elasticity of substitution.
Keywords: C65; E43; G12; 330; term premia; consumption-based models; habit; long-run risk; limited arbitrage; high consumption volatility; recursive utility; solution methods